Biopolymeric fibrous scaffolds for tissue engineering - Yu, Chin Chong. (2010)
Biopolymeric fibrous scaffolds made from biodegradable materials serves to mimic the extracellular matrix (ECM) which provides the cells with the appropriate biological environment for embryologic development, organogenesis, cell growth, and wound repair.